A comparative study of strength and hardness of two motorcycle spoke wheels - Muhammad Arif Khaidir; Fadelan Fadelan; Rizal Arifin (University of Muhammadiyah Jakarta, 2022)
The wheels are a vital component for safety in driving as well as supporting the vertical load of the vehicle when the vehicle is rotating or at rest and serves as a continuation of the rotary motion of the engine to move from one place to another. These wheels are used in a motorcycle made from ironand aluminum alloys material.We perform the tensile and hardness test to obtain their strength and hardness value. We found from our measurement that the maximum tensile stress for the aluminium and iron velg are 155.08 MPa and 277.62 MPa, respectively. The values are directly proportional with the hardness of those material, in which the hardness of iron velg is much higher than that one of aluminium velg by 521.8 VHN.